Research support: Slick city farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Millions of women and men are now farming in cities (see Spore 77). They are growing crops on unused land by roadsides and on perilous rooftops, raising animals in abandoned buildings, and recycling organic wastes into compost.Most city farmers are...